2020
DOI: 10.1021/acs.jpcc.0c07445
|View full text |Cite
|
Sign up to set email alerts
|

Argon Cluster Sputtering Reveals Internal Chemical Distribution in Submicron Polymeric Particles

Abstract: The ability to measure the internal chemical distribution of particles is of significant benefit to the development and testing of products relevant to the pharmaceutical, agrichemical, and food industries. These include nanomedicine particle carriers, such as those used in anticancer drugs, vaccines, and viral carriers for gene therapies. In this work, we carefully investigated the sputtering behavior of spherical organic particles using an argon cluster beam and scanning electron microscopy (SEM). Based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…89 For the largest particle type (with a shell thickness of 35.5 nm), the core could not be detected and sputter depth profiling using argon cluster ions was necessary to obtain detail on the internal distribution of the materials. 91…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…89 For the largest particle type (with a shell thickness of 35.5 nm), the core could not be detected and sputter depth profiling using argon cluster ions was necessary to obtain detail on the internal distribution of the materials. 91…”
Section: Resultsmentioning
confidence: 99%
“…89 For the largest particle type (with a shell thickness of 35.5 nm), the core could not be detected and sputter depth proling using argon cluster ions was necessary to obtain detail on the internal distribution of the materials. 91 Fig. 12(a) and (b) demonstrate that the core material may be detected for particles with nominal shell thicknesses of 12 nm, 23.5 nm and 35.5 nm using Ga Ka HAXPES.…”
Section: Detection Of Nanoparticle Cores Under Thick Shellsmentioning
confidence: 92%
“…An alternative to this non-destructive approach is soft sputtering with modern Ar cluster ion guns. Therefore, an understanding of the sputtering process is necessary [ 76 ]. All in all, these recent technological innovations can boost the application of XPS for core–shell nanoparticles, especially addressing the question of intermixing which is often controversially discussed [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another exciting possibility to obtain insights into the internal structure of polymer nanoparticles provides modern Ar cluster sputtering which was used for the same PTFE-PMMA core–shell particles presented here. It was definitively shown that the nanoparticles have a complete PMMA shell but with randomly positioned internal cores, which was an assumption in the QUASES simulation [ 76 ]. Using the argon cluster sputtering approach, the total volume fraction of PTFE was accurately measured and, with knowledge of the sputtering yield, the particle diameter could also be estimated.…”
Section: Non-centrosymmetric Ptfe-pmma Core–shell Nanoparticlesmentioning
confidence: 99%
“…In some cases, it is possible to use XPS to obtain calibration data for SIMS, and this has been useful, for example, in interpreting SIMS data from sputterdepth profiling of organic core-shell nanoparticles. 27 The application of SIMS to drug delivery vehicles 11,[28][29][30][31][32][33][34][35][36][37][38][39] is an important area where simple quantification schemes are required as well as in the analysis of a number of technical products. 40,41 In the case of more complicated, multicomponent and multiphase materials such as biological samples, these methods are not applicable but represent a step on the road to obtaining quantitative information.…”
Section: Discussionmentioning
confidence: 99%